IMPLEMENTASI KEPALA MADRASAH SEBAGAI LEADER DAN EDUCATOR DI MA RAUDLATUL ULUM PUTRI - Syauqillah, Muhammad; Tazkiyah, Ianatut; Anggarini, Ida Fitri; Qur'ana, Faridah Amiliyatul; Abidin, Munirul (STAI Ma'had Aly Al-Hikam Malang, 2023)
The head of a professional madrasah is the head of a madrasa who can carry out his main duties in accordance with regulations, so as to carry out his role in managing and developing the madrasah comprehensively. There are many roles of the madrasah head covered in the acronym EMASLIM-FM. The purpose of this study is to know the implementation of the role of the head of the madrasah as a Leader in MA Raudlatul Ulum Putri, 2) know the implementation of the role of the head of the madrasah as an Educator in MA Raudlatul Ulum Putri. The approach to this research is descriptive qualitative with a type of case study. The research was conducted from October-December 2022 at MA Raudlatul Ulum Putri Ganjaran Gondanglegi Malang. The data collection is through observation, interviews, and documentation. The data analysis technique is data reduction, presentation, and verification (conclusion). The results of this study are: 1) the implementation of the role of the head of the madrasah as a leader in MA Raudlatul Ulum Putri is the existence of pathfinding by planning and having a madrasa vision and mission, aligning that prioritizes verbal social relations with stakeholders, empowering the madrasah by being a good and authoritative person so that he can be a role model for his subordinates in the madrasah, 2) the implementation of the role of the head of the madrasah as an educator in MA Raudlatul Ulum Putri is The head performs his role as a guide for students in the classroom by teaching as many as 6 hours of lessons, and other educator tasks guide teachers, education staff, staff following the development of science and technology, and become an example in the learning process.Keywords. Educator; Headmaster; Leader.